Influence of menstrual phase and symptoms on match running in professional footballers - Brown, G. A.; Duffield, R. (Scandinavian Journal of Medicine & Science in Sports, 2024)
This study examined the effects of menstrual cycle phases and symptoms on match running performance in football (soccer) players. Twenty-one nonhormonal contraceptive using football players from four professional teams were monitored for up to four menstrual cycles during a domestic league season. Menstrual phases, classified as early-follicular phase (EFP), mid-late follicular phase (MFP), and luteal phase (LP), were determined by self-reporting of menstruation and urinary hormone tests (luteinizing hormone and pregnanediol-3-glucuronide). On match day, players completed a menstrual symptom severity questionnaire. In repeated matches, players wore 10 Hz Global Positioning Satellite (GPS) devices to measure relative (/min) total distance, high-speed running distance, very high-speed distance, peak speed, acceleration count, and deceleration count. Linear mixed models were performed for each GPS measure to determine the relationship with phase or symptoms. Data for 7 and 10 players were included for menstrual phase and menstrual symptoms analyses, respectively. A significantly higher total distance was reported during MFP compared to EFP (Delta 5.1 m min-1; p = 0.04) and LP (Delta 5.8 m min-1; p = 0.007). Significantly greater high-speed running was reported during MFP compared to EFP (Delta 1.2 m min-1; p = 0.012) and LP (Delta 1.1 m min-1; p = 0.007). No significant effect of menstrual phase was found for any other GPS measures (p > 0.05). Accelerations declined with increasing symptom severity (p = 0.021, estimate = -0.01count.min-1). Menstrual symptom severity did not affect any other GPS measures (p > 0.05). In conclusion, greater total distance and high-speed running occurred during the MFP. Additionally, accelerations minimally decreased with increasing menstrual symptom severity. Large intra- and inter-variability existed, suggesting individualized monitoring and management of menstrual effects on performance would be beneficial.